Expedient synthesis of heterocycles and methyl sulfonyl compounds via C-X BONDS (X = O, N, S) construction - Jiang, Yaojia (2015)
In this thesis, we have described new strategies for the synthesis of heterocycles including furans, 2H-azirines, pyrroles, and pyridines through construction of C–O and C–N bonds, respectively as well as novel approaches to synthesis of methyl sulfonyl compounds including β-keto methyl sulfones and (E)-vinyl methyl sulfones through C–S bond construction. In chapter 1, we have described diverse transformations of α-diazo-β-keto compounds into furans and 2H-azirines in the presence of transition metal catalysts. In chapter 2, we have described two methodologies for the synthesis of highly substituted pyrroles from a common substrate, α-diazo-β-keto oxime ethers, involving 2-vinyl-2H-azirines as key intermediates. In chapter 3, we have described two methodologies to synthesize multi-substituted pyridines from rhodium-catalyzed nitrene reaction and DBU-mediated ring opening of 2-allyl-2H-azirines. In chapter 4, we have described a radical strategy promoted by copper, oxygen and HPO(OEt)2 for the difunctionalization of alkenes to synthesize β-keto methyl sulfones; meanwhile, we have also demonstrated that alkynes could be directly undergo methyl sulfonylation to afford (E)-vinyl methyl sulfones through modification of the reaction condition.